Putting and Keeping Students on Track: Toward a Comprehensive Model of College Persistence and Goal Attainment. Issue 1 (June 2013) - Burrus, Jeremy; Elliott, Diane; Brenneman, Meghan; Markle, Ross; Carney, Lauren; Moore, Gabrielle; Betancourt, Anthony; Jackson, Teresa; Robbins, Steve; Kyllonen, Patrick; Roberts, Richard D.
Abstract: Despite near universal acceptance in the value of higher education for individuals and society, college persistence rates in 4‐year and community colleges are low. Only 57% of students who began college at a 4–year institution in 2001 had completed a bachelor's degree by 2007, and only 28% of community college students who started school in 2005 had completed a degree 4 years later (National Center for Education Statistics, 2011). To address this problem, this paper identified 3 goals. The first was to review the extant literature on persistence in higher education. The second was to develop a working model of persistence informed by our literature review. This resulted in a model centered on 3 basic categories of variables: those that put you on track towards persistence, those that push you off track, and those that keep you on track. The final goal was to outline a research agenda to develop student‐centered assessments informed by our model, and we conclude with a discussion of this agenda.